(1-x)^1/2 = sqrt (1-x)
Then just do the chain rule
-.5(1-x)^-.5
2007-07-18 08:01:18
·
answer #1
·
answered by misscarinne 4
·
0⤊
0⤋
let 1-x=u
then you have u^1/2
derivative of u^1/2 is 1/2u^-1/2(du)
(du) is the derivative of u which is -1 from the derivative of -x
so you have d(sqrt(1-x))=1/(2sqrt(1-x))
2007-07-18 15:03:13
·
answer #2
·
answered by Kris Z 4
·
0⤊
0⤋
that would be.... (1/2)(-1)/sqrt(1-x)....
so basically you got (1-x)^(1/2)/// so bring the 1/2 down...
derive (1-x)... and subtract 1 from 1/2.. so that it is -1/2
then (1/2)(-1)/sqrt(1-x)........... where -1 is der of 1-x
2007-07-18 15:03:03
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
-1/2*sqrt(1-x)
2007-07-18 15:07:03
·
answer #4
·
answered by ? 5
·
0⤊
0⤋
derivative of u^a = au^(a-1) * du
so u = 1-x, and derivative of (1-x)^.5 = .5(1-x)^(-.5) * (-1) =
-.5(1-x)^(-.5) = -.5/sqrt(1-x)
2007-07-18 15:05:33
·
answer #5
·
answered by John V 6
·
0⤊
0⤋
It is -0.5/sqrt(1-x).
2007-07-18 15:01:13
·
answer #6
·
answered by mikeburns55 5
·
0⤊
0⤋
y = f (x) = (1 - x)^(1/2)
dy/dx = f `(x) = (1/2) [(1 - x) ^(-1/2) ] (-1)
dy/dx = f `(x) = (- 1/2) / â(1 - x)
2007-07-22 02:53:24
·
answer #7
·
answered by Como 7
·
0⤊
0⤋
(1/2)(1-x)^(-1/2)(-1) = -1/(2sqrt(1-x))
2007-07-18 15:02:32
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋